A.06 Ataluren: an overview of clinical trial results in nonsense mutation Duchenne Muscular Dystrophy (nmDMD). (17th June 2016) - McDonald, CM; Bushby, K; Tulinius, M; Finkel, R; Topaloglu, H; Day, JW; Flanigan, K; Lowes, L; Eagle, M; Luo, X; Elfring, G; Kroger, H; et al.
Abstract : Background : Ataluren is the first drug to treat the underlying cause of nmDMD.Methods: Phase 2 and 3 studies of ataluren in nmDMD were reviewed, with efficacy and safety/tolerability findings summarized.Results: Ataluren nmDMD trials include: a Phase 2a proof-of-concept study (N=38); a Phase 2b randomized controlled trial (RCT) (N=174); an ongoing US-based open-label safety extension study (N=108); an ongoing non-US-based open-label safety/efficacy extension study (N=94); and a Phase 3 RCT, ACT DMD (N=228), whose primary endpoint was change in six-minute walk distance (6MWD) over 48 weeks. The proof-of-concept study demonstrated increased dystrophin production in post-treatment muscle biopsies from ataluren-treated patients with nmDMD. The Phase 2b results demonstrated an ataluren treatment effect in 6MWD, timed function tests, and other measures of physical functioning, The Phase 3 ACT DMD results demonstrated an ataluren treatment effect in patients with nmDMD in both primary and secondary endpoints, particularly in those with a baseline 6MWD of 300-400m. Ataluren was consistently well-tolerated in all three trials, as well as in the ongoing extension studies. Trial findings will be presented in detail.Conclusions: The totality of the results demonstrates that ataluren enables nonsense mutation readthrough in the dystrophin mRNA, producing functional dystrophin and slowing disease progression. Supported by: PTC Therapeutics Inc.